Effects of a Self-Compassion Break Induction on Self-Reported Stress, Self-Compassion, and Depressed Mood. Issue 5 (October 2020) - Williamson, Jessica
Introduction: The objective of the study was to determine whether practicing a self-compassion induction would reduce self-reported stress, depressed mood, and increase self-compassion in a randomized controlled study measuring variables of interest at two time points spanning three weeks. Method: Participants were 129 students (91 females and 38 males, M age = 19.47, SD = 3.20) divided into three groups: Self-compassion Break, Time Management Control Group, and a No-Induction Control Group. Participants were part of the general student body and were not diagnosed or screened for clinical depression. Self-compassion, stress, and depressed mood were assessed at baseline and follow-up. Participants practiced their respective inductions over three weeks after being guided through their respective inductions at Time 1. Results: There were no significant differences between groups in outcome variables. Results of this study may indicate the importance of weekly group check-in meetings to facilitate positive change as findings in this study did not mirror those of similar studies using frequent meetings.